Garbo the spy [videorecording (DVD)] - Roch, Edmon; West, Nigel; Seaman, Mark; Vinader, Xavier (First Run Features, 2012)
The Allies called him Garbo. The Nazis dubbed him Alaric. Both sides in World War II were sure Juan Pujol Garcia was their man. In reality, Pujol was a double agent, and his final allegiance was to the Allies. From the comfort of Lisbon, Garbo fed false information to the Nazis and fabricated a network of phantom agents across Europe. Although he never fired a single shot, Garbo helped to save thousands of lives, most notably by misinforming the Germans about the timing and location of D-Day.